The expressed representation of pronominal subject in PB topic-coment sentences - da Silva, Edila Vianna (2020)
This article analyzes the occurrence of pronominal subject in topic-comment sentences in Brazilian portuguese, from an oral language corpus. Considering the frequency with which these structures appear in the Brazilian variant and the fact that there are many common characteristics between topic languages and Portuguese, we will establish a relationship between topic sentences and the expressed representation of pronominal subject, taking into account the discursive need to fill the subject in these structures, as well as the context in which this filling is not necessary. The study was carried out based on a qualitative analysis of the selected corpus, which confirmed the initial hypothesis that, even in cases in which the pronominal subject can be elliptical, the speaker, in most cases, chooses to complete it, which points to the presence, more and more frequent, of the pronominal subject expressed in the BP.